Three Generations, Two Solitudes, and One Big Drop - Lussier, Patrick (Canadian journal of criminology and criminal justice, 2023)
A research project aiming to measure, describe, and monitor sex offender recidivism (SOR) rates across two waves of sex offender laws is briefly described and contextualized. A methodology was designed to examine the evolution of sexual recidivism rates since the 1940s. The findings of the study showed that, in Canada, sexual recidivism rates have dropped almost 70%. This historic recidivism drop appeared to have started during the 1970s, several decades before the enactment of the national non-public sex offender registration law. While the factors responsible for the sexual recidivism drop remain unclear, it is hypothesized that improved training, evidence-based practices, and university-corrections collaborations might have played a key role. The study points toward the importance of examining period effects on risk, risk management, and sexual offending.